Quasi-Static Torsion Characterization of Micro-diameter Copper Wires - Lu, W.-Y.; Song, B. (Experimental mechanics, 2011)
A method to measure very small torques that subject micro-diameter copper wires to plasticity is developed for quasi-static torsion experiment. Following the concept in the work by Fleck et al. (Acta Metall. Mater. 42:2, 1994 ), we employed a glass fiber filament as the torque cell. To calculate the small torques applied on the micro-diameter copper wires, an additional rotation sensor is required to measure the rotation of the glass fiber torque cell. The rotation sensor system is attached between the glass fiber and the copper wire specimen. It uses a laser extensometer to gauge the distance between a helical and a horizontal reflection tapes on a foam cylinder, which is calibrated with the angle of rotation. A new set of torsional experimental data for the copper wires with four different diameters, from 16–180 μm, are presented. All copper wires exhibit a typical elastic-plastic response. The torsional properties of these copper wires were not found to be significantly different. The uncertainties of the measurement and analysis are discussed.